Clinical and ultrasound characteristics of surgically removed adnexal lesions with largest diameter ≤ 2.5 cm: a pictorial essay. (5th November 2017) - Di Legge, A.; Pollastri, P.; Mancari, R.; Ludovisi, M.; Mascilini, F.; Franchi, D.; Jurkovic, D.; Coccia, M. E.; Timmerman, D.; Scambia, G.; Testa, A.; Valentin, L.
ABSTRACT: Objectives: To describe the ultrasound characteristics, indications for surgery and histological diagnoses of surgically removed adnexal masses with a largest diameter of ≤ 2.5 cm (very small tumors), to estimate the sensitivity and specificity of diagnosis of malignancy by subjective assessment of ultrasound images of very small tumors and to present a collection of ultrasound images of surgically removed very small tumors, with emphasis on those causing diagnostic difficulty. Methods: Information on surgically removed adnexal tumors with a largest diameter of ≤ 2.5 cm was retrieved from the ultrasound databases of seven participating centers. The ultrasound images were described using the International Ovarian Tumor Analysis terminology. The original diagnosis, based on subjective assessment of the ultrasound images by the ultrasound examiner, was used to calculate the sensitivity and specificity of diagnosis of malignancy. Results: Of the 129 identified adnexal masses with largest diameter ≤ 2.5 cm, 104 (81%) were benign, 15 (12%) borderline malignant and 10 (8%) invasive tumors. The main indication for performing surgery was suspicion of malignancy in 22% (23/104) of the benign tumors and in all 25 malignant tumors. None of the malignant tumors was a unilocular cyst ( vs 50% of the benign tumors), all malignancies contained solid components ( vs 43% of the benign tumors), 80% of the borderline tumors had papillary projections ( vs 21% of the benign tumors and 20% of the invasive malignancies) and all invasive tumors and 80% of the borderline tumors were vascularized on color/power Doppler examination ( vs 44% of the benign tumors). The ovarian crescent sign was present in 85% of the benign tumors, 80% of the borderline tumors and 50% of the invasive malignancies. The sensitivity of diagnosis of malignancy by subjective assessment of ultrasound images was 100% (25/25) and the specificity was 86% (89/104). Excluding unilocular cysts, the specificity was 71% (37/52). Analysis of images illustrated the difficulty in distinguishing benign from borderline very small cysts with papillations and benign from malignant very small well vascularized (color score 3 or 4) solid adnexal tumors. Conclusions: Very small malignant tumors manifest generally accepted ultrasound signs of malignancy. Small unilocular cysts are usually benign, while small non‐unilocular masses, particularly ones with solid components, incur a risk of malignancy and pose a clinical dilemma. © 2016 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.